Engineering a colorimetric yeast-based assay to detect small molecules in the gastrointestinal system - Dacquay, Louis C.; Samman, Bana; Newman, Matthew P.; Philpott, Dana J.; McMillen, David R. (Frontiers in Synthetic Biology, 2024)
The procedures involved in diagnoses of intestinal diseases are often costly, invasive, expensive and dependent on specific technical expertise; these factors can hinder clinicians’ efforts to monitor and treat inflammatory bowel disease and other conditions. Simpler, less expensive and more widely accessible methods could help evaluate the efficacy of treatments and assess the risk of relapse. Yeast, including the probiotic strain Saccharomyces boulardii, can access the gastrointestinal tract, coming into contact with otherwise difficult-to-access disease biomarkers. These yeast cells can be recovered from patient stool samples after ingestion and used to report on prevailing conditions within the gastrointestinal tract during their passage. Here, we report a yeast-based assay offering a simple output based on colour change of colonies plated from recovered stool samples and demonstrate that the reporter can respond to an externally-supplied small-molecule signal while passing through the gastrointestinal system of mice.